I had a problem with solving the following;

$f(x-2)+f(x+2)=f(x)$ I have tried to make it look like $f(x+T)=f(x)$ but I failed. I mostly have difficulty in solving these type of problems. What do you suggest I should do?


2 Answers 2


Hint. We have that $$f(x+2)+f(x+6)=f(x+4) $$ and $$ f(x)+f(x+4)=f(x+2) .$$ By adding them, we get $$ f(x)+f(x+6)=0\implies f(x+6)=-f(x).$$
Therefore $$f(x+12)=f((x+6)+6)=-f(x+6)=f(x)$$ for any real $x$ and we may conclude that a period of the function is $12$.

  • $\begingroup$ Thank you:) How did you get to the last part where $-f(x+6)=f(x+12)$? $\endgroup$ Aug 26, 2017 at 9:25
  • $\begingroup$ @DenizTunaYalçın Substituting $x + 6$ for $x$ in the equation $f(x + 6) = -f(x)$ yields $f(x + 12) = f(x + 6 + 6) = -f(x + 6)$. $\endgroup$ Aug 26, 2017 at 9:33
  • $\begingroup$ May I ask what is the final conclusion ? That the set of solutions is exactly the set of periodical functions $\mathbb R \to \mathbb R$ with period 12 ? $\endgroup$
    – Jean Marie
    Aug 26, 2017 at 9:44
  • $\begingroup$ @Jean Marie Yes, If $f$ is not identically zero, try to show that the period can't be a proper divisor of $12$. $\endgroup$
    – Robert Z
    Aug 26, 2017 at 9:54

Using this, the characteristic equation of $$f(x+2)-f(x)+f(x-2)=0$$

$t^4-t^2+1=0, t=e^{(2m+1)\pi i/6}$ where $m=0,2,3,5$

$$\implies f(x)=\sum_{m=\{0,2,3,5\}}A_me^{(2m+1)\pi ix/6}$$

Now if $f(x)=f(x+T)\forall x,$ we need $$e^{(2m+1)\pi ix/6}=e^{(2m+1)\pi i(x+T)/6}$$

$\implies\dfrac{(2m+1)\pi T}6\equiv0\pmod{2\pi}$


As $(2m+1,12)=1$ for $m=0,2,3,5,$ we need $$T\equiv0\pmod{12}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.